Recent advances in quantum dot-based light-emitting devices: Challenges and possible solutions. (April 2019) - Yang, Zhiwen; Gao, Mengyu; Wu, Weijie; Yang, Xuyong; Sun, Xiao Wei; Zhang, Jianhua; Wang, Hung-Chia; Liu, Ru-Shi; Han, Chang-Yeol; Yang, Heesun; Li, Wanwan
Graphical abstract: Abstract: Colloidal quantum dots (QDs) have been generating substantial interest due to their unique properties, which include high quantum efficiency, high color purity, low-cost solution processability, as well as an easily tunable emission wavelength. They are considered to be alternative emissive materials for next-generation light-emitting diodes (LEDs) in lighting and display applications. However, there are several factors that limit the performance of QLEDs, such as nonradiative recombination, energy transfer, and field-induced quenching. Additionally, past research has primarily focused on Cd-based quantum dots, which also limits their commercialization. Due to the development of nanotechnology, tremendous progress has been made regarding the synthesis methods of QDs, the understanding of QD properties, the application of QD in LEDs, and exploring the challenges and possible solutions of high efficiency. In this review, we begin with a general introduction of the development of organic LEDs, inorganic LEDs, and QLEDs. Subsequently, we demonstrate the challenges of QDs for high-efficiency LEDs, and describe possible solutions including interface engineering, inter-dots distance control, large Stokes shift QD designing, encapsulation engineering, device architecture designing, as well as heavy metal free QD exploring. Finally, we conclude with a discussion regarding the future prospects of QLEDs.